Senescent cells: A new Achilles' heel to exploit for cancer medicine?. Issue 1 (19th November 2018) - Zhang, Boyi; Lam, Eric W.‐F.; Sun, Yu
Abstract: Cellular senescence is a typical tumor‐suppressive mechanism that restricts the proliferation of premalignant cells. However, mounting evidence suggests that senescent cells, which also persist in vivo, can promote the incidence of aging‐related disorders principally via the senescence‐associated secretory phenotype (SASP), among which cancer is particularly devastating. Despite the beneficial effects of the SASP on certain physiological events such as wound healing and tissue repair, more studies have demonstrated that senescent cells can substantially contribute to pathological conditions and accelerate disease exacerbation, particularly cancer resistance, relapse and metastasis. To limit the detrimental properties while retaining the beneficial aspects of senescent cells, research advancements that support screening, design and optimization of anti‐aging therapeutic agents are in rapid progress in the setting of prospective development of clinical strategies, which together represent a new wave of efforts to control human malignancies or mitigate degenerative complications.